Firefly island [large type] : a novel - Wingate, Lisa (Center Point Large Print, 2013)
Congressional staffer Mallory Hale is about to embark on an adventure completely off the map. After a whirlwind romance, she is hopelessly in love with two men-- fortunately, they're related.